Appraisals in Students’ Hortatory Exposition Essays - Refnaldi Refnaldi (International Conference on Languages and Arts, 2012)
This paper aims at describing how appraisals are used by the writer in using the language components for the purpose of developing discussion texts. The focus of the analysis is how the three appraisal sub-systems—attitude, engagement, and graduation—are taught to students. Attitude itself will be further divided into affect, judgment, and appreciation. Engagement is also classified into two, mono-gloss and hetero-gloss. Graduation is, furthermore, subcategorized into force (gradable) and focus (non-graded). Moreover, the functions performed by appraisals used are classified into three positioning, attitudinal positioning, dialogistic positioning, and intertextual positioning.